2022
DOI: 10.21037/jgo-22-884
|View full text |Cite
|
Sign up to set email alerts
|

Impact of caregiver burden on caregiver mental health in patients with esophageal cancer: chain mediating effects of benefit finding and rumination, a cross-sectional study

Abstract: Background: Cancer caregivers are the main supporter for the tumor patients, they not only need to provide daily nursing to the patients, but also suffering the pressure from economy, emotion and even family members. The mental health of tumor patient is mostly noticed, while not caregivers. The mental health of caregiver greatly affected the nursing quality and even the treatment outcomes. In the current study, the mechanisms underlying the links between caregiver burden, benefit finding, mental health, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…In a 2013 UK study with 842 breast cancer patient caregivers, BF was significantly negatively correlated with the psychological distress of caregivers [48]. Another 2022 Chinese study of 228 esophageal cancer patient caregivers suggested that the caregivers' BF played a mediating role in the anxiety-depression of the caregivers [12]. We suggested that a higher level of BF might lower the psychological distress of caregivers, which could lead to a lower prevalence of depression.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In a 2013 UK study with 842 breast cancer patient caregivers, BF was significantly negatively correlated with the psychological distress of caregivers [48]. Another 2022 Chinese study of 228 esophageal cancer patient caregivers suggested that the caregivers' BF played a mediating role in the anxiety-depression of the caregivers [12]. We suggested that a higher level of BF might lower the psychological distress of caregivers, which could lead to a lower prevalence of depression.…”
Section: Discussionmentioning
confidence: 74%
“…We found that lower BF level, higher demoralization severity, and higher stigma severity were associated with depression among PD caregivers. Several studies have shown a correlation between BF and depressive symptoms among caregivers [12,48]. In a 2013 UK study with 842 breast cancer patient caregivers, BF was significantly negatively correlated with the psychological distress of caregivers [48].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have reported the relationship between negative self-focus with anxiety, stress and depression. [46][47][48][49] Nevertheless, they have been detected only in non-caregivers' sample and caregivers of brain-injured and mentally ill patients. While these specific coping strategies may be more prevalent in certain groups (eg, non-caregivers and mental caregivers) we have proven that they are effective for caregivers, regardless of the specific situation.…”
Section: Discussionmentioning
confidence: 99%
“…Benefit finding assists patients in cultivating inner peace and acceptance, enabling them to better cope with the realities of the disease and approach their life journey with a positive mindset. This inner peace and acceptance help patients establish more solid internal support, leading to higher levels of satisfaction and tranquillity at a spiritual level (Wen et al., 2022 ). Carrico's research on HIV‐positive individuals found that benefit findings can influence spiritual well‐being to a greater extent, enabling individuals to more effectively manage the cumulative effects of HIV infection (Carrico et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%